The The Microbiological Quality of Drinking Water from the Regional Drinking Water Company (PDAM) in the Service Unit of Wungu, Madiun Regency - Afifah Muhdotul Febriana Safitri (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2023)
One of the requirements for water quality is the absence of Coliform bacteria. Coliform is a type of bacteria commonly used as an indicator of animal or human fecal pollution and poor water conditions, where the presence of these bacteria can signal whether a water source has been contaminated by pathogens or not. The local water utility (PDAM) wants to determine if there are still Coliform bacteria present in the water flow by collecting complaints and feedback from the surrounding community. The objective of this research is to assess the presence of Coliform in the drinking water supplied by PDAM in the Wungu Service Unit, Madiun Regency, as one of the microbiological quality criteria. The method employed in this study is a qualitative and descriptive approach, conducted by testing water samples in the laboratory using the Most Probable Number (MPN) method. A total of 16 samples were collected from 8 repetitions at 2 different stations. The results showed that 8 samples tested positive for Coliform bacteria, while 8 samples tested negative. It can be concluded that the two stations fail to meet the criteria established by the Ministry of Health Number 2 Of 2023 Year and indicate that the water contains Coliform bacteria suspected to originate from the soil.